Interfacial stability and atomistic processes in the a-c/si(100) heterostructure system - Gioti, Maria; Logothetidis, Stergios D.; Kelires, Pantelis C. (My University, 1999)
We study the interfacial properties of thin amorphous carbon films grown on silicon (100) substrates. By combining experimental spectroscopic ellipsometry and stress measurements and theoretical Monte Carlo simulations, we show that significant interdiffusion takes place at the initial stages of growth, driven by a strain mediated mechanism, and we identify the relevant atomistic processes.
Keywords: Heterostructures; Carbon; Ellipsometry